2017
DOI: 10.1371/journal.pone.0189507
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants in Sjögren’s syndrome patients: A systematic review

Abstract: ObjectivesThe Sjögren’s syndrome (SS) is a chronic autoimmune disease that affects salivation and consequently the health of oral tissues. The aim of this systematic review was to investigate the implant survival rate, marginal bone loss (MBL) and biological complications of dental implants in SS patients.Materials and methodsEligibility criteria included prospective and retrospective cohort studies, controlled clinical trials, and randomized clinical trials (RCTs). An electronic search without date or languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 46 publications
0
36
0
2
Order By: Relevance
“…The present study aimed to assess the clinical outcome of dental implants in a series of patients with SS, as well as to review the cases of SS patients receiving dental implants described in the literature. In relation to previous reviews on the subject, 27,28 the present study performed a more careful systematic search of the literature, thus resulting in greater number of included studies. Systematic reviews are insufficiently informative if they do not include all available current evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to assess the clinical outcome of dental implants in a series of patients with SS, as well as to review the cases of SS patients receiving dental implants described in the literature. In relation to previous reviews on the subject, 27,28 the present study performed a more careful systematic search of the literature, thus resulting in greater number of included studies. Systematic reviews are insufficiently informative if they do not include all available current evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the high prevalence of sSS, it is likely that dentists will encounter sSS patients in their daily practice. 3 It is fundamental to bear in mind the lower success rates of the dental implant in patients with SS compared to healthy patients; however, improving the patient'squality of life with the appropriate dental implant treatment plan is similarly essential. It has been reported that the self-confidence and oral function of the SS patients, will significantly improve with implant-supported prostheses compared with removable complete dentures.…”
Section: Discussionmentioning
confidence: 99%
“…S jögren’s syndrome (SS) is a systemic autoimmune disease characterized by lymphocytic infiltration of exocrine glands, with salivary and lacrimal glands being the most commonly involved sites. 1 SS is diagnosed more frequently in women with 9:1 female/male ratio and has two points of incidence around 30-40 and 50-60 years of age, 2 , 3 and is categorized into primary or secondary SS caused by systemic diseases such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), systemic sclerosis (SSc) and, autoimmune liver or thyroid diseases. 4 Progressive immune-mediated destruction of the disease affects several organs of the body including articular joints, central nervous system, lungs, and skin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sjogren's Syndrome (SS) is a chronic autoimmune disease that affects salivation and consequently the health of oral tissues at incidence of 0.2% of the population, a systemic review gave an average of 93.7% survival of implants in such patient's group [1,2]. And they are good candidate for implants as they can't wear dentures owning to the lack of saliva and sensitive mucosa [2].…”
Section: Introductionmentioning
confidence: 99%